Characterization of human induced pluripotent stem cells line (PNUSCRi004-A) from a Parkinson’s disease patient carrying L483P, A495P and V499V mutations - Hye-Ji Moon; Nayeon Lee; Ji-Young Moon; Jae-Hyeok Lee; Jae-Ho Kim (Stem Cell Research, 2023)
The hiPSC line was generated from peripheral blood mononuclear cells (PBMCs) collected from a female patient with young onset Parkinson’s disease (PD), carrying on heterozygous c.1448 T > C (L483P), c1483 G > C (A495P) and c.1497 G > C (V499V) mutations in the GBA gene. The PBMCs was reprogrammed into an induced pluripotent stem cell (iPSC) line (GBA PD8 or PNUSCRi004-A hiPSCs) using non-integrative Sendai virus. The cell line, PNUSCRi004-A displayed a normal karyotype and expression of pluripotency markers capable of producing derivatives of three germ layers (Ectoderm, Endoderm and Mesoderm).